2012
DOI: 10.1007/s12010-012-9775-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bioimprinted Tannase and Its Kinetic and Thermodynamics Properties in Synthesis of Propyl Gallate by Transesterification in Anhydrous Medium

Abstract: Tannase has been extensively applied to synthesize gallic acid esters. Bioimprinting technique can evidently enhance transesterification-catalyzing performance of tannase. In order to promote the practical utilization of the modified tannase, a few enzymatic characteristics of the enzyme and its kinetic and thermodynamics properties in synthesis of propyl gallate by transesterification in anhydrous medium have been studied. The investigations of pH and temperature found that the imprinted tannase holds an opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…On the contrary, cold-active enzyme showed that its thermolability is entropically driven [33]. The energy of activation E a(d) for irreversible thermal inactivation of A. oryzae tannase was (163.37 kJ mol −1 , calculated from Fig 9) was higher than the previous recorded values for other tannases [34]. These results indicate that more energy is required to inactivate the enzyme and hence implied to be more thermostable.…”
Section: Thermal Stability and Thermodynamics Of Irreversible Inactivmentioning
confidence: 63%
“…On the contrary, cold-active enzyme showed that its thermolability is entropically driven [33]. The energy of activation E a(d) for irreversible thermal inactivation of A. oryzae tannase was (163.37 kJ mol −1 , calculated from Fig 9) was higher than the previous recorded values for other tannases [34]. These results indicate that more energy is required to inactivate the enzyme and hence implied to be more thermostable.…”
Section: Thermal Stability and Thermodynamics Of Irreversible Inactivmentioning
confidence: 63%